El fragmentado reconocimiento de la terminación unilateral en los contratos de consumo en el Derecho de Consumo chileno - Isler Soto, Erika (Pontificia Universidad Católica del Perú, 2024)
The article analyzed the regulation of the unilateral termination of the contract in Chilean Consumer Law, reaching the conclusion that its treatment is fragmentary and inorganic. However, unilateral termination is regulated whether it is based on the law or based on the contract. In the first case, it is granted solely and imperatively to the consumer, as a weak subject of the consumer relationship, under the figures of retract and withdrawal. There are, however, important differences between one and the other, linked to the eventual validity of an expiration period, the way in which it operates and its scope of application. The unilateral withdrawal enshrined by the pact is considered illicit if it is established exclusively in favor of the entrepreneur and lawful if its beneficiary is the consumer. When the power is conferred on both parties of the consumer relationship, its legality will have to be judged according to whether or not it generates a significant imbalance for the parties and whether it complies with the standards of good faith.

El artículo analizó la regulación de la terminación unilateral del contrato en el Derecho de Consumo chileno, arribándose a la conclusión de que su tratamiento es fragmentario e inorgánico. Con todo, se regula la terminación unilateral tanto si tiene por fuente la ley como si se sustenta en el contrato. En el primer caso, se lo concede únicamente y de manera imperativa al consumidor, en tanto sujeto débil de la relación de consumo, bajo las figuras del retracto y el desistimiento. Existen no obstante diferencias importantes entre una y otra, vinculadas con la eventual vigencia de un plazo de caducidad, la forma en que opera y su ámbito de aplicación. El retiro unilateral consagrado mediante el pacto es considerado ilícito si se establece únicamente en favor del proveedor y lícito si su beneficiario es el consumidor. Cuando la facultad es conferida a ambas partes de la relación de consumo, su juridicidad habrá de ser enjuiciada según si genera o no un desequilibrio importante para las partes y si se ajusta a los estándares de la buena fe.
The fragmented recognition of unilateral termination in consumer contracts in Chilean Consumer Law
Keywords: Consumer; Consumer legal link; Unilateral termination of contract; Retract; Termination of contract; Abusive clause; Consumer law; Chile; Consumidor; Relación de consumo; Terminación unilateral del contrato; Retracto; Desistimiento; Cláusula abusiva; Derecho de consumo; Chile; https://purl.org/pe-repo/ocde/ford#5.05.00